The role of local initiatives and social networks in solving the problem of waste disposal in the cities of Apatity and Kirovsk, Murmansk region: the experience of participant observation - N. A. Koldobskaya (Цифровая социология)
The study is devoted to identifying the role of local initiatives and local communities in solving garbage problems in the cities of Apatity and Kirovsk in the Murmansk region. The cases of Apatity and Kirovsk show that the basis for the consolidation of the local community as a socio-territorial community is the place of residence and the use of existing social structures, in this case, localized neighboring communities, Internet communities and their communication channels. The interviews conducted at the field stage in the cities showed that thanks to local initiatives, in parallel to the actions of regional operators, there is a process of transformation of ecological thinking and the formation of a certain mentality. In each city, more and more people are involved in the process of cleaning the territory from garbage and separate collection of waste. In many ways, urban initiatives in Kirovsk and Apatity in the conditions of urban shrinkage exist not because of, but in spite of the socio-economic processes that are taking place there. Most of the citizens involved in the process note that it is very important for them to make their city better and feel like a part of something in common, to feel their need.